The concession of the BR-163 highway in the Brazilian Amazon: Corporatization of territory and conflicts - Cardoso Rodrigues, Jondison; Nahum, João Santos (DIE ERDE – Journal of the Geographical Society of Berlin, 2023)
The BR-163 highway in the Brazilian Amazon has become one of the most important corridors for the Brazilian ag- ribusiness sector. It is a highway that synchronizes times, flows, logics, and economic chains, especially with its total paving in 2019, and its concession to the private sector in 2022. This article seeks to synthesize and analyze the complex recent and future territorial manifestations of the BR-163 concession (Sinop/Mato Grosso to Itaituba/Miritituba/Pará). The concession of the highway is a driver and inducer of new spatial orders and the expansion of corporate uses of theterritory. Deforestation, land grabbing, violence and conflicts are already observable and the future scenario is its expansion. Thus, new governance arrangements are needed to push towards a variety of discursive and material prac- tices: the respect for the laws, the environment, the different cultures. These arrangements would be important ways to promote territorial and food security for the Amazon peoples.